Integral Solution of the Interface Profile of Grain Boundary Grooving by Surface Diffusion - Caifang Wang; Hui Xing; Fengping Yao; Changle Chen; Jianyuan Wang; Fei Fan (Advances in Materials Science and Engineering)
In polycrystalline thin films, formation of grain boundary grooving is investigated widely due to its effects on their properties. Infinite series solution of the interface of grain-boundary grooving by surface diffusion has been obtained. In this paper, with Fourier transform, a novel integral solution of the profile of grain boundary grooving is derived. Numerical examples are taken to test the performance of the integral solution. According to the numerical examples, we find that the novel solution is in accordance with the infinite series solution.